Airway responsiveness to psychological processes in asthma and health - Ritz, Thomas (Frontiers in Physiology, 2012)
Psychosocial factors have been found to impact airway pathophysiology in respiratory disease with considerable consistency. Influences on airway mechanics have been studied particularly well. The goal of this article is to review the literature on airway responses to psychological stimulation, discuss potential pathways of influence, and present a well-established emotion-induction paradigm to study airway obstruction elicited by unpleasant stimuli. Observational studies have found systematic associations between lung function and daily mood changes. The laboratory –based paradigm of bronchoconstrictive suggestion has been used successfully to elicit airway obstruction in a substantial proportion of asthmatic individuals. Other studies have demonstrated an enhancement of airway responses to standard airway challenges with exercise, allergens, or methacholine. Standardized emotion-induction techniques have consistently shown airway constriction during unpleasant stimulation, with surgery, blood and injury stimuli being particularly powerful. Findings with various forms of stress induction have been more mixed. A number of methodological factors may account for variability across studies, such as choice of measurement technique, temporal association between stimulation and measurement, and the specific quality and intensity of the stimulus material, in particular the extent of implied action-orientation. Research has also begun to elucidate physiological processes associated with psychologically induced airway responses, with vagal excitation and ventilatory influences being the most likely candidate pathways, whereas the role of specific central nervous system pathways and inflammatory processes has been less studied. The technique of emotion-induction using films has the potential to become a standardized challenge paradigm for the further exploration of airway hyperresponsiveness mediated by central nervous system processes.